Cycle Index of the Symmetry Group of Fullerenes C24 and C150 - GHORBANI, MODJTABA; REZA ASHRAFI, ALI (Asian Journal of Chemistry, 2010)
The three-dimensional polya cycle indices for the natural actions of the symmetry group of the small fullerene C24 and big fullerene C150 over the set of vertices, edges and faces are computed.